Influence of Combined Application of Inorganic N and P Fertilizers and Cattle Manure on Quality and Shelf-Life of Potato (Solanum tuberosum L.) Tubers - Masrie Z, Biruk; Dechassa R, Nigussie; Abebie, Bekele; Alemayehu, Yibekal; Tana, Tamado (Journal of Postharvest Technology, 2014)
Potato tuber qualities, including dry matter content, specific gravity, total soluble solids, and crude protein content, are important parameters for human consumption. Tuber physiological weight loss, rotting, and sprouting during storage are important aspects that influence the keeping quality of the crop for profitable production. These tuber quality parameters can be affected by fertilizer management in the sense that inadequate or excess fertilizer application reduces tuber quality and shelf life. Therefore, a study was conducted during two successive cropping seasons of 2012 and 2013 to determine the effect of combined application of nitrogen, phosphorus, and cattle manure on potato tuber quality and shelf-life during storage.